CORRECTION OF ASTHENO-VEGETATIVE SYMPTOMS OF THE POST-COVID SYNDROME BY PHYSICAL THERAPY IN THE POSTPARTUM PERIOD IN WOMEN WHO UNDERWENT CAESAREAN SECTION - Ostap’iak, Z. M.; Vypasniak, I. P.; Polataiko, Yu. O.; Oleksiuk, L. I.; Petryk, O. M. (Rehabilitation and Recreation, 2023)
Purpose: to determine the effectiveness of restoring the health status of women with post-COVID-19 syndrome who underwent cesarean section, according to the dynamics of indicators of astheno-vegetative syndrome. Methods. 44 women were examined at the beginning of the late postpartum period. The control group consisted of 15 women who gave birth vaginally and did not suffer from COVID-19 during pregnancy and observation. The comparison group consisted of 15 women after caesarean section who suffered from COVID-19 during pregnancy, recovered during pregnancy and the postpartum period according to general recommendations for the rehabilitation of patients with coronavirus infection. The main group consisted of 14 women after caesarean section, suffered from COVID-19 during pregnancy, and performed a proven physical therapy program for 2 months (therapeutic exercises, elements of yoga; massage; aromatherapy sessions; autogenic training sessions). The condition of women was assessed according to the results of the Wayne questionnaire, Epworth sleepiness scale, Fatigue Assessment Scale, Fatigue Severity Scale. Results. During the initial examination, signs of autonomic dysfunction (according to the Wayne questionnaire), increased fatigue (according to the Fatigue Assessment Scale, Fatigue Severity Scale), and abnormal sleepiness (according to the Epworth sleepiness scale), were most pronounced in women with post-COVID-19 syndrome. During the re-examination, the best result in terms of all studied parameters was found by women of the control group, demonstrating a normal course of the postpartum period. The results of the women of the main group on the investigated indicators of astheno-vegetative syndrome were statistically significantly better (p<0.05) than those of the women of the comparison group. Conclusions. The use of physical therapy, taking into account the course of astheno-vegetative syndrome, is pathogenetically and practically justified in the process of physical therapy of women with post-COVID-19 syndrome in the postpartum period after abdominal delivery in order to improve the vegetative status, reduce the feeling of fatigue and weakness, and reduce pathological drowsiness.